2010
DOI: 10.1002/app.32927
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on isothermal crystallization, melting behaviors, and spherulitic morphologies of multiblock copolymers containing poly(butylene succinate) and poly(1,2‐propylene succinate)

Abstract: In this article, isothermal crystallization, melting behaviors, and spherulitic morphologies of highimpact multiblock copolymers, comprising of PBS as hard segment and poly(1,2-propylene succinate) (PPSu) as soft segment with hexamethylene diisocyanate as a chain extender, were investigated. The results from differential scanning calorimetry (DSC) suggest that the two segments of multiblock copolymers are miscible in amorphous region. The crystallization kinetics were analyzed by the Avrami equation. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…In the previous reports, PPS was termed as amorphous block in PBS- co -PPS without providing any diffraction information. Based on the analysis of glass transition temperature, it was proposed that PPS block is miscible with the amorphous phase of PBS. Here we present a more systematic investigation on the microstructure of PBS- co -PPS. Figure shows the WAXS intensity profiles of PBS- co -PPS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous reports, PPS was termed as amorphous block in PBS- co -PPS without providing any diffraction information. Based on the analysis of glass transition temperature, it was proposed that PPS block is miscible with the amorphous phase of PBS. Here we present a more systematic investigation on the microstructure of PBS- co -PPS. Figure shows the WAXS intensity profiles of PBS- co -PPS.…”
Section: Resultsmentioning
confidence: 99%
“…The T g of PBS- co -PPS is higher than that of PBS homopolymer, which increases with the PPS content. The T g * listed in Table is estimated by the Fox equation 1 T g * = 1 w normal P P S * T g , PBS + w PPS * T g , PPS where T g, PBS and T g, PPS are 240.55 and 267.85 K, respectively. The weight fraction of PPS ( w * PPS ) is calculated taking account of the crystallinity of the system: w PPS * = w PPS 1 X normalc It can be observed that the measured T g deviated from the estimated T g * remarkably as the PPS fraction increasing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators thought that the Peak I corresponded to the melting subsidiary lamellae and it was due to the melting of the material crystallized previously. Meanwhile, the Peak II corresponded to the melting the recrystallization . According to Hoffman–Weeks theory , the equilibrium melting temperature T m 0 was obtained by extrapolating the line of the temperature of Peak I versus T c to the line of T m = T c .…”
Section: Resultsmentioning
confidence: 99%
“…The aim of designing copolymers is to improve the homopolymer properties and to achieve better processability, chemical resistance and higher mechanical properties. In fact, final and favorable modified properties of copolymers can be achieved, depending on the type, amount and distribution of the comonomer units along the polymer chain . More recently, the mechanical properties of PBS were improved through preparation of biodegradable PBS multiblock copolymers via copolycondensation of succinic acid and butandiol with low molecular weight poly(ethylene oxide) or via chain extension of PBS with other hydroxy‐terminated polymers, such as poly(1,2‐propylene succinate) or poly(1,2‐propylene terephthalate), or through melt mixing of PBS and poly(triethylene succinate) .…”
Section: Introductionmentioning
confidence: 99%